A web-based intervention (RESTORE) to support self-management of cancer-related fatigue following primary cancer treatment: a multi-centre proof of concept randomised controlled trial - Foster, Claire; Grimmett, Chloe; May, Christine M.; Ewings, Sean; Myall, Michelle; Hulme, Claire; Smith, Peter W.; Powers, Cassandra; Calman, Lynn; Armes, Jo; Breckons, Matthew; Corner, Jessica; et al. (Springer, 2015)
Purpose: Cancer-related fatigue (CRF) is a frequent and distressing symptom experienced after cancer treatment. RESTORE is the first web-based resource designed to enhance self-efficacy to manage CRF following curative-intent treatment. The aim of this study is to test the proof of concept and inform the design of an effectiveness trial.